The Description of Mathematics Learning for Grade IV of Muhammadiyah Islamic Elementary School of Krendetan - Meliana Wulandari, Meliana Wulandari; Sapti, Mujiyem; Rizkia Pangestika, Rintis (IJPSE : Indonesian Journal of Primary Science Education, 2021)
This research is entitled to describe the mathematics online learning for grades IV of Muhammadiyah Islamic Elemetary School of Krendetan. This research requires some sources such as the school principal, the classroom teachers, and the student guardians. The research design uses qualitative research design. The study collects data by using direct research, data from sources, and real evidence. The instruments in this study included: observation sheets, interview guides, and documentation checklists. The results of this study indicate that (1) there is a principal's policy in mathematics online learning for grade IV of Muhammadiyah Islamic Elemetary School of Krendetan. He has an important policy in implementing Mathematics online learning. The school principal conducts some socializations to the school association, the principal and the curriculum team to arrange learning tools such as lesson plans, syllabus, annual program, and semester program. (2) There is a role of the teacher in implementing mathematics online learning. The teacher’s role is like preparing learning tools such as lesson plans, syllabus, annual program, and semester program. The teaching and learning process starts from 07.00 a.m to 12.00 a.m. the stes are first, filling out forums for student absences and the teacher provides learning videos that contain materials and assignments that students must do. After completing the assignment, the students can collect but the teacher also provides a collection limit which is until 21.00 a,m. The assignment is given by the teacher by knowing the ability of students to solve problems according to how it works. (3) There is a role of the student’s guardian in implementing mathematics online learning. The implementation of mathematics online learning for grade IV is carried out from 07.00 a.m to 12.00 a.m by filling in the student attedance list and the teacher send the subject matter in the form of a video to be listened. After listening, the students then do the assignments given by the teacher. After completing the assignmnet, the students send assignments along with photos of students while studying.